Experiential brand positioning: Developing positioning strategies for beach destinations using online reviews - Viriya Taecharungroj (2022)
This research analysed tourist experiences on beaches and suggested appropriate brand positioning for Thai beach destinations. A new destination positioning method was proposed involving a topic modelling algorithm, hierarchical clustering and textual analysis using data from 75,500 TripAdvisor reviews. Eleven tourist experiences and five clusters of distinctive beach destinations were identified. Findings suggested that the Tourism Authority of Thailand should replace their current “all-in-one” message with strategic and relevant communications to strengthen brand positioning by reinforcing the positive experiences and improving the negative aspects of beach tourism. Experiential brand positioning can assist DMOs to differentiate destinations as multi-faceted and dynamic.